Effects of testosterone administration on liver structure and function in aging rats - Baptista Nucci, Ricardo Aparecido; Souza Teodoro, Ana Caroline de; Neto, Walter Krause; Silva, Wellington de Assis; Souza, Romeu Rodrigues de; Anaruma, Carlos Alberto [UNESP]; Gama, Eliane Florencio (Taylor & Francis Ltd, 2017)
Aging males have a decrease in testosterone levels, by which the testosterone treatment may influence in a negatively fashion the liver.Aim: This study aimed to analyze the effects of aging with or without testosterone administration on the liver components of animals.Methods: Wistar rats were divided into three groups: 20 months' group (G20), 24 months' group (G24), group treated with testosterone for 16 weeks (GT). All groups were sacrificed at 24 months except for G20 that was sacrificed at 20 months.Results: Aging and testosterone treatment alters the body weight (BW), liver weight (LW) and relative liver weight. Besides, testosterone increased the mitogen capacity of hepatocytes. Nonetheless, we reinforce the negative effects of testosterone on old animals' liver as chronic hepatic congestion and/or cholestasis. In addition, we observed that testosterone plays an important role on hepatic glycogen stores.Conclusions: Our study showed many implications for the knowledge about the effects of aging with or without testosterone administration on old animals' liver.
Keywords: Liver; aging; testosterone; hepatic structure; male hormone